2009
DOI: 10.1519/jsc.0b013e3181b8d246
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Muscle Activation and Force Generation Patterns During Cycling Movements Because of Low-Intensity Squat Training With Slow Movement and Tonic Force Generation

Abstract: Our previous studies showed that relatively low-load (approximately 50-60% 1 repetition maximum [1RM]) resistance training with slow movement and tonic force generation (LST) significantly increased muscle size and strength. However, LST is a very specific movement that differs from natural movements associated with sport activities and activities of daily life, and therefore, it might have some unfavorable effects on dynamic sport movement. We investigated the effects of LST on muscle activity and force gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(34 citation statements)
references
References 20 publications
1
24
0
9
Order By: Relevance
“…important neuromuscular function in various physical activities and also contributes to reducing the incidence of falling or slipping, especially in elderly populations [2]. Tanimoto et al [26] also observed that a 13-week LST program in the leg muscles changed muscle activation and force generation patterns during dynamic (cycling) movements to be more tonic. This suggests that LST may have unfavorable effects on dynamic power production, since more instantaneous (i. e., less tonic) muscle activation is important for achieving high power [1], especially during dynamic explosive movements.…”
Section: Introduction ▼mentioning
confidence: 99%
“…important neuromuscular function in various physical activities and also contributes to reducing the incidence of falling or slipping, especially in elderly populations [2]. Tanimoto et al [26] also observed that a 13-week LST program in the leg muscles changed muscle activation and force generation patterns during dynamic (cycling) movements to be more tonic. This suggests that LST may have unfavorable effects on dynamic power production, since more instantaneous (i. e., less tonic) muscle activation is important for achieving high power [1], especially during dynamic explosive movements.…”
Section: Introduction ▼mentioning
confidence: 99%
“…Conversely, the LST protocol has an unfavorable effect on dynamic sports movements . Thus, this type of exercise might be ineffective for improving motor function in the activities of daily life of the elderly, such as walking and climbing stairs.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, the LST protocol has an unfavorable effect on dynamic sports movements. 21 Thus, this type of exercise might be ineffective for improving motor function in the activities of daily life of the elderly, such as walking and climbing stairs. For comprehensive improvement of physical function, the LST protocol should be combined with exercises that specialize in improving the nervous system, such as plyometric exercise, which improves muscle power and physical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Tanimoto et al . reported that the slow movement protocol had a detrimental effect on dynamic sports movements . Therefore, several quickly performed exercises were included in this CGIP .…”
Section: Discussionmentioning
confidence: 99%
“…Tanimoto et al reported that the slow movement protocol had a detrimental effect on dynamic sports movements. 53 Therefore, several quickly performed exercises were included in this CGIP. 27 The post-intervention questionnaire also showed that the CS group conducted the quick leg raise and quick squats significantly more than the HB group (P < 0.01: unpresented data) when performing the programme in daily life.…”
Section: Discussionmentioning
confidence: 99%